Empathy as a Tool for Evangelism in Sapele Metropolis: A Theological Evaluation of Luke 7:11-17 - Idoro, Okeoghene Emmanuel; Enuwosa, Joseph (dialektika kontemporer, 2024)
Empathy is the ability to understand and relate to others' feelings and experiences. This research aims to examine how Jesus demonstrated empathy in his ministry and how modern Christians demonstrate empathy in their evangelical commitments. The study focuses on Luke 7:11-17, a narrative of Jesus' encounter with a funeral procession in Nain, and how his compassion for the weeping widow demonstrates his mercy and compassion. It explores the theological expression of empathy in the context of evangelism by churches in Nigeria, specifically in Sapele metropolis. The study employs biblical exegesis, literature review, and oral interviews to evaluate Luke 7:11-17 and its application to evangelism. The research encourages church leaders, particularly women, to have a heart for reaching out to widows and create awareness about the challenges faced by bereaved widows. The study promotes the use of empathy as a viable tool for evangelism in modern churches, particularly in the context of women.